Changing Role of Dalit Women at the Community Level - Tamata, Hira; Bishwakarma, Lila Bahadur; Khatri, Bishnu Bahadur; Pasa, Rajan Binayek (GS Spark: Journal of Applied Academic Discourse, 2023)
This paper examines the changing role of Dalit women at the community level, particularly in Shikhar Municipality of Doti, far west region. The study collected data from 132 respondents selected randomly using the quantitative case study method. The study found that the awareness level of Dalit women has increased, motivating them to improve their socio-economic status in the community. They are becoming skillful, independent, and change agents, working against social stigma, and playing decision-making roles in the household and community levels. They are gaining power, advancing capacity, and influencing social practices that advance the interests of other Dalit and Non-Dalit women such as empathy, collaboration, open-mindedness, fairness, and kindness. Additionally, Dalit women are playing economic, socio-cultural, and leadership roles against paradox due to the implementation of a target budget program that offers technical/financial support to them. The study recommends increasing the size of the target budget for Dalit women’s entrepreneurship development throughout the country.